Analisis Determinan Indeks Pembangunan Manusia di Aceh - Nurlina Nurlina; Miswar Miswar; Aldwifa Nugraha (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to determine the effect of unemployment, economic growth, education and health sector government spending on the Human Development Index in Aceh. The data used in this study is secondary data from the Central Bureau of Statistics (BPS), the data used is the 20082019 period. The method of analysis used in this study is multiple linear regression analysis using statistical tests to determine the 95% degree of confidence. (???? = 0.05) on the t test. The results of this study indicate that partially the unemployment variable has a positive and insignificant effect, the Economic Growth variable has a positive and significant effect, the Education Sector Government Expenditure variable has a positive and insignificant effect and the Education Sector Government Expenditure has a negative and significant effect on the Human Development Index in Aceh. Then simultaneously it has a positive and insignificant effect on the Human Development Index in Aceh.